Hard Work Conquers All: Building the Finnish Community in Canada - Harpelle, Ronald N.; Ratz, David K.; Beaulieu, Michel S. (UBC Press, 2018)
Above the entrance to the Finnish Labour Temple, in what was once Port Arthur in northern Ontario, is the motto labor omnia vincit – “hard work conquers all.” Since 1910, these words have reflected the dedication of the Finnish community in Canada. This book is a social history of Finnish immigration and community building in Canada during the twentieth century. The first Finns to arrive ranged from conservative churchgoers to radical socialists, reflecting the ideologies that divided their homeland. After the First World War, left-wing Finns fled persecution; following the Second World War, Finns sought the economic security that Canada offered. Each new wave of immigration imbued the relationship between people, homeland, and host country with the politics, ideologies, and cultural expressions of its time. The story of Finns in Canada dovetails with the larger literature on immigration and enriches the history of socialism and ethnic repression in this country. The insightful essays in Hard Work Conquers All explore the nuanced cultural identities of Finnish Canadians, their continued ties to Finland, intergenerational cultural transfer, and the community’s connections with socialism and labour movements. This is a fresh interpretation of the successive waves of Finnish immigration and their influence on Canadian politics and society. --Publisher's description
Keywords: 1900-1999; Canada; Canadiens d'origine finlandaise; Canadiens d'origine finlandaise Conditions sociales 20e siècle; Canadiens d'origine finlandaise Conditions économiques 20e siècle; Canadiens d'origine finlandaise Mœurs et coutumes 20e siècle; Finnish Canadians; Finnish Canadians Economic conditions 20th century; Finnish Canadians Social conditions 20th century; Finnish Canadians Social life and customs 20th century; Finns; Finns Canada; Finns Canada Economic conditions 20th century; Finns Canada Social conditions 20th century; Finns Canada Social life and customs 20th century; Finns Social conditions; Finns Social life and customs